Properties of Aspalathus linearis extracts as sunscreen agents in combination with standard UV filters - Aguilera-Arjona, José; Sepúlveda, Pablo; López Sánchez, Ana; Haya, Luisa; González, Salvador; De-Gálvez-Aranda, María Victoria (Springer, 2026)
The new horizons in sunscreen development are based on the discovery of novel active ingredients, and those from natural sources are the most promising. The objective of the work was to analyze the potential of different Aspalathus linearis (AL) extracts as natural photoprotective ingredients to be used in combination with standard UV filters in topical formulas. The impact of AL extracts on different biological protection factors, as well as on the photostability of standard organic UV filters, was measured. Under this aim, and employing in vitro techniques, UV transmittance properties, solar protection factor, UVA protection factor, and immune protection factor were analyzed for the extracts formulated alone or in combination with the UVB and UVA standard filters Octyl-methoxy-cinnamate (OMC) and Butyl-Methoxy-dibenzoyl-methane (BMDBM). Water containing AL extracts showed a significant UV absorbance in the entire UV spectrum with an absorption peak around 285 nm. The addition of AL extracts to sunscreen galenic formulas, including OMC and BMDBM, increased the protection factors up to 50%. AL extracts were also able to protect BMDBM and OMC against photodegradation under increasing radiation doses up to 14.4 standard erythemal doses. In conclusion, the addition of AL extracts in topical photoprotective formulas provides the double benefit of increasing the protection values against different biological effects, as well as improving photostability. Thus, these natural extracts appear as valuable candidates for the development of safer and more efficient sunscreens.
Keywords: Dermatología - Fórmulas y recetas; Protectores solares; Sunscreens; Natural extracts; Booster; Solar protection factor; Biological protection factors; Photostability